Radiofrequency Ablation of Thyroid Nodules: Basic Principles and Clinical Application. (22nd October 2012) - Shin, Ji Hoon; Baek, Jung Hwan; Ha, Eun Ju; Lee, Jeong Hyun
Abstract : Radiofrequency (RF) ablation has been gaining popularity as a minimally invasive treatment for benign thyroid nodules regardless of the extent of the solid component. RF ablation of benign nodules demonstrated volume reductions of 33–58% after one month and 51–85% after six months, while solving nodule-related clinical problems. RF ablation has recently shown positive short-term results for locoregional control as well as symptom improvement in patients with recurrent thyroid cancers. This paper reviews the basic physics, indications, patient preparation, devices, procedures, clinical results, and complications of RF ablation.